Immune checkpoint inhibitors in advanced and relapsed/refractory Hodgkin lymphoma: current applications and future prospects - Milrod, Charles J.; Pelcovits, Ari; Ollila, Thomas A. (Frontiers in Oncology, 2024)
Classic Hodgkin lymphoma (cHL) treatment paradigms are undergoing a shift with the integration of immune checkpoint inhibitors (ICIs) into both first-line and relapsed/refractory (R/R) regimens. In first-line therapy, the synergy between ICIs and chemotherapy may surpass the previous standards of ABVD and BV-AVD established by landmark trials including RATHL and ECHELON-1. In R/R disease, the combination of ICIs with chemotherapy has begun to challenge the paradigm of chemotherapy as a bridge to consolidative autologous stem cell transplantation. The clinical advances heralded by ICI offer unique challenges to management. ICI treatment and the associated inflammatory response can make the traditional timing and modalities of treatment response assessment difficult to interpret. In contrast to ABVD and BV-AVD, pembrolizumab-AVD results in PET2 positivity rates that are higher and less predictive of treatment response even when ultimate outcomes may be superior. This suggests that the predictive value of PET2 may be less reliable in the ICI era, prompting a reevaluation of response assessment strategies. Looking forward, circulating tumor DNA (ctDNA) may be a promising tool in response-adapted therapy. Its potential to complement or even supersede PET scans in predicting response to ICIs represents a critical advancement. The integration of ctDNA analysis holds the promise of refining response-adapted approaches and enhancing precision in therapeutic decision-making for patients with cHL. This review navigates the evolving landscape of cHL therapy, emphasizing the paradigmatic shift brought about by ICIs. This article explores the impact of combining ICIs with chemotherapy in both relapsed/refractory and first-line settings, scrutinizes the challenges posed to response-adapted therapy by ICIs, and highlights the potential role of ctDNA as an adjunct in refining response-adapted strategies for cHL.